Nutritional Peak Week and Competition Day Strategies of Competitive Natural Bodybuilders - Andrew J. Chappell; Trevor N. Simper (MDPI AG, 2018)
Bodybuilders utilize peaking strategies in a bid to fine-tune their aesthetics for competition day. The most prevalent peaking strategies utilized by natural bodybuilders are unreported in the current literature. Eighty-one (M-59, F-22) natural bodybuilders were recruited from competitions during the 2016 and 2017 British Natural Bodybuilder Federation seasons. Competitors completed a 34-item questionnaire designed to investigate peaking and contest day strategies. The questionnaire listed commonly utilized peaking strategies and provided additional space for qualitative information. Analysis of the data indicated that carbohydrate (CHO), water, and sodium manipulation were the most commonly utilized peaking strategies. The consumption of high glycemic index CHO was the most common competition day strategy. Only 6.2% of competitors reported following their regular diet the week prior to competition. The CHO manipulation strategies followed were similar to classical CHO loading, whereby bodybuilders attempt to maximize muscle glycogen concentrations. Furthermore, bodybuilders attempted to remove superfluous water by exploiting the diuretic/polyuria effect associated with water loading/restriction. The potentially deleterious effects of peaking on bodybuilders’ health is considered and the efficacy of these strategies to enhance appearance is discussed. The findings of the present investigation are likely to be of interest to bodybuilders and their coaches.